Synthesis of 1, 2, 3‐Triazole‐Linked Hexopyranosylpyrimidine Nucleosides and Their Application as Hepatitis B Viral DNA, HBsAg and HBeAg Suppressants. Issue 12 (21st March 2023) - Verma, Vineet; Singh, Ankita; Tyagi, Purnima; Kumar, Vijay; Prasad, Ashok K.
Abstract: A series of novel 1, 2, 3‐triazole‐linked hexopyranosyl mono/double‐headed pyrimidine nucleosides from D‐glucose was synthesized by Cu(I)‐mediated [3+2] cycloaddition reactions (CuAAC) of mono/diazido 2, 6‐anhydro‐glucoheptitol and propynylated pyrimidines in good yields. It was observed that all the four synthesized pyrimidine nucleosides were found to be non‐cytotoxic upto 500 μM concentration. The 1, 2, 3‐triazole‐linked hexopyranosyl mono/double‐headed pyrimidine nucleosides have shown significant suppression of Hepatitis B surface antigen (HBsAg) and Hepatitis B e‐antigen (HBeAg). Amongst all the synthesized compounds, nucleoside dimer 1‐[1‐(6′‐deoxy‐6′‐(4‐(1‐methyluracil)‐1, 2, 3‐triazol‐1‐yl) ‐β ‐D‐glucopyranosyl methyl)‐1, 2, 3‐triazol‐4‐yl]methyl‐uracil was found to be more effective against HBeAg. In the suppression of viral DNA level, all the four synthesized nucleoside analogues were comparable to known drug Entecavir (ETV) with IC50 value in the range of 8.39 μM–18.58 μM and are two folds significant as compared to control. Abstract : 1, 2, 3‐triazole‐linked pyrimidine nucleosides were synthesized as a result of Cu(I)‐mediated [3+2] cycloaddition (CuAAC) reaction of mono/diazido 2, 6‐anhydro‐glucoheptitol and propynylated pyrimidines.The synthesized nucleoside analogues can be utilized as HBsAg suppressants, HBeAg suppressants and Hepatitis B viral DNA suppressants.